ANALISIS MERKURI (Hg) PADA LOTION PEMUTIH YANG BEREDAR DI PASAR RAYA KOTA PADANG MENGGUNAKAN SPEKTROFOTOMETER SERAPAN ATOM - Afdhil Arel; Regina Andayani; Aulia Rahmi; Wida Ningsih (Universitas Wahid Hasyim Semarang, 2019)
ABSTRACT Whitening lotion is a mixture of chemicals or other ingredients with properties that can whiten the skin or blemish black (brown) on the skin. The use of mercury in whitening lotions can cause a variety of things, ranging from skin discoloration which can ultimately cause black spots on the skin, allergies and skin irritation. The using of mercury in high dose can cause permanent brain damageand cancer. An analysis of mercury content in the whitening lotion brands A, B and C circulating at market in Padang city has been conducted. Extraction of mercury in the whitening lotion was done by wet destruction with a concentrated HNO3 solution and concentrated H2SO4 for 2 hours at a temperature of ± 95°C until a clear solution is obtained. The clear solution was measured by absorption with an Atomic Absorption Spectrophotometer using a mercury hollow cathode lamp at a wavelength of 253.7 nm. The results of this study were samples of brands A, B and C detected containing mercury metals with successive levels of 0.3347 μg /g; 0,7917 μg /g and 0,7981 μg/ g. The whitening lotions that circulate in market do not meet the Head of BPOM RI Regulation No.18 of 2015 whose contents prohibit the use of mercury in cosmetics preparations. Keywords: mercury, whitening lotion, Atomic Absorption Spectrophotometer